2016
DOI: 10.3168/jds.2015-10716
|View full text |Cite
|
Sign up to set email alerts
|

Effect of difructose anhydride III supplementation on passive immunoglobulin G transfer and serum immunoglobulin G concentration in newborn Holstein calves fed pooled colostrum

Abstract: Difructose anhydride (DFA) III acts on intestinal epithelial tight junctions and promotes calcium absorption through the paracellular pathway in dairy cows. This trial was done to investigate the effects of DFA III supplementation on passive IgG transfer and serum IgG concentration in calves. Twenty-four newborn Holstein male calves were grouped as 12 pairs, with each pair receiving a separate batch of pooled colostrum (PC) from the first 2 milkings. One calf from each pair was allocated to the treatment group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…at 36 h of age, as reported in previous studies (Weaver et al, 2000;Furman-Fratczak et al, 2011). The peak serum IgG concentration was higher in calves fed colostrum with DFA III than in calves fed colostrum without DFA III, consistent with our previous studies (Sato et al, 2012;Htun et al, 2016). In addition to the peak serum IgG concentration, AEA was higher in the treatment group than in the control group.…”
Section: Effect Of Dfa III On Igg Absorption and Serum Igg Concentrationsupporting
confidence: 91%
See 2 more Smart Citations
“…at 36 h of age, as reported in previous studies (Weaver et al, 2000;Furman-Fratczak et al, 2011). The peak serum IgG concentration was higher in calves fed colostrum with DFA III than in calves fed colostrum without DFA III, consistent with our previous studies (Sato et al, 2012;Htun et al, 2016). In addition to the peak serum IgG concentration, AEA was higher in the treatment group than in the control group.…”
Section: Effect Of Dfa III On Igg Absorption and Serum Igg Concentrationsupporting
confidence: 91%
“…Difructose anhydride (DFA) III is a plant-derived, indigestible oligosaccharide that can promote calcium absorption through paracellular pathways in the intestine of rats (Mineo et al, 2004) and cattle (Teramura et al, 2015). We previously reported that supplementation of DFA III in colostrum fed to newborn calves improved absorption of colostral IgG and increased serum IgG concentrations (Sato et al, 2012;Htun et al, 2016). It has been suggested that the increase of peak serum IgG concentration after colostrum feeding could be due to improved intestinal paracellular pathway via loosening the tight junctions between intestinal epithelial cells by DFA III (Mineo et al, 2004) for greater IgG absorption in newborn calves (Sato et al, 2012;Htun et al, 2016), because DFA III has been shown to improve paracellular absorption in bovine intestine (Teramura et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms behind the improvement in EAE are unknown. Several authors have speculated that the increased absorption of IgG in calves supplemented with DFAIII could be due to an improvement in intestinal absorption through the paracellular pathway by increasing the opening of the epithelial tight junctions [ 22 , 32 , 33 ]. However, Jochims et al [ 19 ] clearly illustrated that intestinal absorption of IgG in calves occurred through micropinocytic transfer.…”
Section: Discussionmentioning
confidence: 99%